The Exclusivism of Religion Teachers: Intolerance and Radicalism in Indonesian Public Schools - Dirga Maulana (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2017)
In the context of Indonesianism and Islamism, religion teachers serve as avant garde of tolerance, which is then manifested into their social contexts. The attitude of religious tolerance and inclusivity are must have for religion teachers; since these teachers have the closest connection to their students who are mostly young people. We have observed that the increasing radicalism in educational institutions has been associated with particular models of interpretation, understanding, teaching, schools of thoughts, denomination, and even sects within a particular religion. For instance, an international agency has reported the discovery of an